2019
DOI: 10.21203/rs.2.13433/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low psoas muscle index is a poor prognostic factor for lower gastrointestinal perforation: a single-center retrospective cohort study

Abstract: Background Various body composition indices have been reported as prognostic factors for different cancers. However, whether body composition affects prognosis after lower gastrointestinal tract perforation requiring emergency surgery and multidisciplinary treatment has not been clarified. This study examined whether body composition evaluations that can be measured easily and quickly from computed tomography (CT) are useful for predicting prognosis. Methods Subjects comprised 64 patients diagnosed with per… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Several studies have demonstrated the negative association between sarcopenia and postoperative outcomes in colorectal cancer patients [14,20,21,36,37], inflammatory bowel disease [38], pancreatic malignancy [27], and following hepatobiliary resection [28]. In a recent retrospective analysis of 350 patients undergoing colorectal cancer resection, Richards et al demonstrated that 32.9% of the cohort was classified as sarcopenic which was consistent with our cohort's sarcopenia rate of 34% [36].…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have demonstrated the negative association between sarcopenia and postoperative outcomes in colorectal cancer patients [14,20,21,36,37], inflammatory bowel disease [38], pancreatic malignancy [27], and following hepatobiliary resection [28]. In a recent retrospective analysis of 350 patients undergoing colorectal cancer resection, Richards et al demonstrated that 32.9% of the cohort was classified as sarcopenic which was consistent with our cohort's sarcopenia rate of 34% [36].…”
Section: Discussionsupporting
confidence: 87%
“…Kasahara et al proved that sarcopenia evaluated by the psoas muscle index was a predictor of overall survival in patients with advanced urothelial carcinoma undergoing chemotherapy [11]. In patients undergoing surgery for lower gastrointestinal perforation, the low psoas muscle index was a predictor of in-hospital mortality and prolonged hospitalization [12]. Using the cut-off for sarcopenia proposed by Hamaguchi et al [20], Nakayama and colleagues found the psoas muscle index to be a predictor of overall and event-free survival in patients with esophageal cancer undergoing neoadjuvant therapy [13].…”
Section: Discussionmentioning
confidence: 99%
“…[10], Kasahara et al [11], Kayano et al [12], Nakayama et al [13], Williet et al [14], Xu et al [15]) listed in table I.…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation